2022
DOI: 10.1128/spectrum.00496-22
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Transmission of a Tigecycline Resistance-Mediating tet (A) Gene Variant from Enterobacter hormaechei via a Two-Step Recombination Process

Abstract: Tigecycline is an important last-resort broad spectrum antimicrobial agent. This study describes the two-step recombination processes resulting in the transfer of the tet (A) variant gene between different plasmids in E. hormaechei , which depicts the role of recombination processes in the generation of UCSs and new plasmids, both carrying a tet (A) variant conferring resistance to tigecycline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have identified the tet (A) variant as the reason for tigecycline resistance in Salmonella, Klebsiella pneumoniae , and Enterobacter hormaechei . 24 , 28 , 29 A previous study found that most of the S . Kentucky ST198.2 isolates carried the tet (A) variant and exhibited resistance to tigecycline.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the tet (A) variant as the reason for tigecycline resistance in Salmonella, Klebsiella pneumoniae , and Enterobacter hormaechei . 24 , 28 , 29 A previous study found that most of the S . Kentucky ST198.2 isolates carried the tet (A) variant and exhibited resistance to tigecycline.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, except for 35 tigecycline resistance strains carrying tet (X4) or tet (X6), the remaining 66 strains carrying tetracycline resistance genes tet (A), tet (J) and tet (M) were also resistant to tigecycline and 80.3% of these strains were Proteus . It has been found that K. pneumoniae and E. hormaechei carrying the tet (A) variant are resistant to tigecycline due to double frameshift mutation of the tet (A) gene ( 41 , 42 ). And the tet (M) variant can make Streptococcus suis resistant to tigecycline ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, tet (X15) conferred resistance to tetracyclines and glycylcyclines ( Li R. et al., 2021 ). New variants of the tet gene are still emerging, with twenty-seven variants isolated in 2021 ( Yu R. et al., 2022 ). These variants were named from tet (X18) to tet (X44) and were obtained from R. anatipestifer ( Umar et al., 2021 ).…”
Section: Transfer Of Tet Genesmentioning
confidence: 99%